Rehabilitation Sanctions Against Addicts and Drug Abuse Victims: Overview of Islamic Criminal Law - Dini Ratna Sari; Muhammad Ridha (Alhurriyah, 2022)
This article was written because rehabilitation sanctions for victims of drug abusers and addicts are not specified in Islamic criminal law in Indonesia. Because drugs are similarly intoxicating and mind-altering under Islamic criminal law, they are referred to (qiyased)asalcohol (khamr) and are punishable by flogging and ta’zir. Neither of the two sanctions addresses treatment or rehabilitation; instead, they emphasise physical penalties and the deterrent effect they have on alcohol-related offenses. The data for this library research was gathered from reference books, encyclopedias, papers, notes, and a variety of publications.This study can be concluded as follows: first, if the defendant is caught red-handed, evidence is found with the use of one day, a positive laboratory certificate for the use of drugs according to the investigator's request, a certificate from a government psychiatrist or psychiatrist appointed by the judge, there is no evidence that the person concerned is involved in the distribution of drugs for addicts. Second, in Islamic law, drugs are qiyased to khamr because the illat(reason)is both intoxicating and depriving the mind. If khamr is the punishment for drinking in Islamic criminal law, ta’zir is the punishment for drug addicts in positive Indonesian law (rehabilitation).Artikel ini ditulis karena sanksi rehabilitasi yang dijatuhkan terhadap korban penyalahguna narkotika dan pecandu narkotika di Indonesia tidak ada dalam hukum pidana Islam. Dalam hukum pidana Islam narkotika diqiyaskan kepada khamar karena illatnya sama-sama memabukkan dan menghilangkan akal seseorang, sehingga sanksi yang diberikan ialah berupa sanksi had seperti dera dan sanksi ta’zir. Dari kedua sanksi tersebut lebih kepada sanksi fisik dan efek jera yang diberikan kepada pelaku khamar tidak ada yang menyinggung mengenai  pengobatan atau rehabilitasi. Penelitian kepustakaan merujukdata dari buku referensi, artikel, catatan, serta berbagai jurnal.Penelitianinidisimpulkan sebagai berikut: pertama, jika terdakwa dalam..keadaan tertangkap tangan, pada waktu...tertangkap tangan ditemukan barang bukti dengan pemakaian satu hari, surat laboratorium positif penggunaan..narkoba sesuai permintaan penyidik, surat keterangan psikiater atau dokter jiwa pemerintah yang ditunjuk hakim, tidak ada bukti bahwa yang.bersangkutan terlibat peredaran.narkotika bagi pecandu. Kedua, dalam hukum Islam narkotika diqiyaskan kepada khamr dikarenakan illatnya sama-sama memabukkan atau menghilangkan akal. Jika dalam hukum pidana Islam hukuman bagi peminum khamr adalah had maka dalam hukum positif Indonesia hukuman pecandu narkotika adalah hukuman ta’zir (rehabilitasi).